Tinjauan Yuridis Pertanggungjawaban Pidana Terhadap Pelaku Penambangan Pasir Ilegal - Ivan Roberth Sitompul; Taufik Siregar; Rizkan Zulyadi (Mahesa Research Center, 2022)
The rise of Illegal Sand Mining is due to the lack of firm action from Law Enforcers and the application of low penalties. This study aims to examine and analyze legal arrangements, criminal liability and the basis for judges' considerations in making decisions against illegal sand mining actors in Decision number 424/Pid.B/LH/2020/PN Kis. This research uses a normative juridical research method which is descriptive analytical. Data collection techniques were carried out based on library research and field research which were analyzed qualitatively. The results show that sand mining in Indonesia is regulated in several laws and regulations, among others, the Law on Environmental Protection and Management, the Law on Mineral and Coal Mining, Government Regulation on Mining Areas and Government Regulation on the Implementation of Mineral Mining Business Activities. and Coal. Criminal liability against perpetrators of illegal sand mining is regulated in Article 158 of Law no. 4 of 2009 concerning Mineral and Coal Mining with a maximum penalty of 10 (ten) years and a maximum fine of 10,000,000,000.00 (Ten Billion Rupiah). The basis for the judge's consideration in imposing the decision Number 424/Pid.B/LH/2020/PN Kis against the Defendant was sentenced to imprisonment for 10 (ten) months and a fine of Rp. 500,000,000.00 (Five hundred million Rupiah) in which the Judge's Decision was deemed too mild does not realize the purpose of punishment itself to provide a deterrent effect.